The O'Reilly Security Conference, New York, NY, 2016 - Adkins, Heather; Bace, Rebecca Gurley; Thieme, Richard (O'Reilly, 2016)
Includes keynote addresses from the conference.
Title and publication information from resource description page (Safari, viewed November 10, 2016)
Keywords: Computer networks -- Congresses -- Access control; Computer networks -- Congresses -- Security measures; Computer security -- Congresses; Réseaux d'ordinateurs; Sécurité; Mesures; Congrès; Sécurité informatique; Congrès; Computer networks; Access control; Computer networks; Security measures; Computer security; Conference papers and proceedings